¿Quién habla de las mujeres en las noticias donde ellas son las protagonistas? (2011)
The aim of this article is to introduce an analysis of the sources that journalists use when women are the news’ protagonists. The quantitative and qualitative research was carried out on national newspapers and local newspaper, “Castilla y León”. With these results, we noticed that news about women, in most cases, are not signed. We checked what kinds of sources are most used for the production of such news and why the author mentions sources differently for men than he does for women.